2016
DOI: 10.1386/jgvw.8.1.83_1
|View full text |Cite
|
Sign up to set email alerts
|

In control or in their shoes? How character attachment differentially influences video game enjoyment and appreciation

Abstract: Emerging perspectives in media psychology have begun to focus on enjoyment and appreciation as unique reactions to entertaining media fare. Past work has found that game elements such as gameplay mechanics and game narrative are significantly associated with both feelings – with play mechanics more aligned with enjoyment and narrative more aligned with appreciation. The current study looks to extend this work by establishing associations between elements of character attachment (CA) and both entertainment outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 0 publications
4
37
0
Order By: Relevance
“…In line with Oliver and colleagues () and Bowman, Rogers, et al (2013), we argue that a number of dimensions of a game's design, as well as of the situation in which a game is played, all contribute to the user experience—both independently and in concert. In order to explain how hedonic and eudaimonic gratifications are obtained from digital games, it is important to identify and properly characterize these individual features, how they relate to each other and to player experiences.…”
Section: Digital Games: Multiple Layers and Multiple Playerssupporting
confidence: 85%
See 2 more Smart Citations
“…In line with Oliver and colleagues () and Bowman, Rogers, et al (2013), we argue that a number of dimensions of a game's design, as well as of the situation in which a game is played, all contribute to the user experience—both independently and in concert. In order to explain how hedonic and eudaimonic gratifications are obtained from digital games, it is important to identify and properly characterize these individual features, how they relate to each other and to player experiences.…”
Section: Digital Games: Multiple Layers and Multiple Playerssupporting
confidence: 85%
“…The satisfaction of relatedness and insight that determined the appreciation of a game, however, largely depended on its story. Another study by Bowman, Rogers, Sherrick, Woolley, and Chung (2013) on the link between character attachment, enjoyment, and appreciation found that a greater sense of control was associated with more enjoyment, and that appreciation varied as a function of perspective taking. Overall, then, the results from these few very recent studies directly focused on digital games and eudaimonic gratifications suggest that games can, indeed, offer more than just hedonic entertainment and that different features of a game are related to different needs.…”
Section: Games and Eudaimonic Gratificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research done by Bowman, Rogers, Sherrick, Woolley, & Chung (2013) suggests that players who feel a sense of responsibility or care for their avatar found their game experiences more Corwin 14 meaningful. They had players report on both their most enjoyable video game experience and their most meaningful video game experience.…”
Section: Corwin 11mentioning
confidence: 99%
“…In their study of avatars, Bowman, Rogers, Sherrick, Woolley, & Chung (2013) found that players who reported on pleasurable or exciting video games tended to feel a greater sense of control over their online avatars. Meanwhile, players who "reported on meaningful video games... were players who tended to feel stronger senses of responsibility over their avatars" (Banks & Bowman, 2013, p. 2).…”
Section: Introductionmentioning
confidence: 99%